How a Firm’s Value Capture Affects Value Creation in Its Ecosystem - John, Kose; Ross, David Gaddis (Academy of Management Review, 2022)
Using a formal model, we develop a theory of how value capture by a firm with market or bargaining power dampens the incentives of other agents in its ecosystem, showing that the implications for v...